First person - Karen Boschen (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Karen Boschen is first author on ' Transcriptomic analyses of gastrulation-stage mouse embryos with differential susceptibility to alcohol', published in DMM. Karen is a postdoctoral trainee in the lab of Dr Scott Parnell at The University of North Carolina at Chapel Hill, Chapel Hill, NC, USA, investigating the cellular mechanisms of prenatal alcohol exposure, and genetic factors that influence risk and resiliency to developing alcohol-related birth defects.